Efektivitas Video terhadap Pelibatan Ayah dalam Pencegahan Stunting di Masa Pandemi Covid 19 - Wafi Nur Muslihatun; Ana Kurniati; Juli Widiyanto (LPPM Universitas Muhammadiyah Riau, 2023)
Stunting shows failure of linear growth and caused by lack of nutritional intake and infection before and after birth. The fathers role in parenting is related to the nutritional status of toddlers. This study aims to prove the influence of father involvement education using video on father's knowledge and involvement in stunting children prevention. It was an analytic study with a quasy experiment design. The study population was all fathers who had the youngest children aged 6-23 months in the Kulon Progo Regency area, Yogyakarta. Data collection with questionarre, analyzed by T Test. The educating using video was really able to increase father's knowledge about stunting prevention in children (p= 0,000). There is an influence of education using video on father's knowledge (p= 0,000), and involvement in stunting prevention in children (p= 0.000). Conclusion: The education using video was increases father’s knowledge and involvement in children stunting prevention.